Toll‐Like Receptor 7 Inactive Ligands Enhanced Cytokine Induction by Conjugation to Weak Antigens. Issue 6 (16th April 2015) - Gao, Dong; Diao, Yuwen; Li, Wang; Gao, Ningning; Liu, Yu; Wang, Zhulin; Jiang, Wenqi; Jin, Guangyi
Abstract Toll‐like receptors (TLRs) 7/8 are key targets in the design and development of small‐molecule drugs serving as anticancer/antiviral agents and vaccine adjuvants. Clinical trials of imiquimod were discontinued owing to its serious adverse side effects. Herein we report the synthesis and biological evaluation of a series of 8‐hydroxy‐2‐(2‐methoxyethoxy)adenine derivatives that cannot induce cytokine production and that lack activity toward TLR 7/8. Their ability to triggering remarkable levels of cytokine production were revealed upon their conjugation with antigens that have weak immunogenicity. This discovery demonstrated that TLR 7 can be activated by coupling an antigen to the terminal carboxyl group at N9 of the inactive ligand adenine analogues. These inactive analogues may be well suited as new adjuvants with superior activity after conjugation, effectively decreasing the side effects caused by conventional adjuvants.